Checklist of parasitic isopods from Brazil: Bopyroidea and Cryptoniscoidea (Isopoda: Cymothoida: Epicaridea) - Ribeiro, Felipe Bezerra; Horch, Amanda Porciuncula (Zootaxa, 2023)
All species of Brazilian parasitic isopods belonging to Epicaridea (Bopyroidea and Cryptoniscoidea) known to date, including references and distribution information, are listed. The list comprises 37 valid species, 18 of which are endemic to the country, 17 are also recorded from other countries in the Americas, and only two species are distributed outside of the American continent as well. Synonym list, known hosts and distribution are given for each of the species, along with taxonomic and ecological remarks when relevant.